Day-ahead dispatch of integrated electric-heat systems considering weather-parameter-driven residential thermal demands. (15th July 2020) - Wang, Cheng; Liu, Chuang; Lin, Yuzhang; Bi, Tianshu
Abstract: Weather parameters, such as outdoor temperature, solar radiation, and wind velocity, not only affect the residential thermal demands (RTDs) but also are the key influencing factors of renewable power generation outputs (RPGOs). This paper aims to make up for the insufficient modeling efforts in coordinating the endogenous correlated RTDs and RPGOs for the scheduling of the integrated electric-heat system (IEHS). The tractable residential thermal balance equation is derived considering the impacts of weather parameters. Then, a scenario-based two-stage stochastic dispatch model for the IEHS is proposed, where the regional weather parameters are employed to generate the scenarios of the RTDs and RPGOs. The simulation results verify the necessity of considering multiple weather parameters in RTD modeling, as well as coordinating RTDs and RPGOs in IEHS dispatch. Highlights: The thermal demand model considering three types of weather parameters is proposed. The correlation among thermal demands and renewable generation outputs is captured. A scenario-based two-stage stochastic dispatch model for the IEHS is proposed. The significances of the source-load correlation modeling is revealed.